The correlated influence of semantic types, L1 translation equivalents and language proficiency on EFL learners' production of polysemous words - Qu, Chunhong (Frontiers in Psychology, 2023)
The current research investigated the influencing factors of the full mastery of L2 (English) polysemous words with a Chinese-English translation test. The concepts of "meaning" and "L2 equivalent" were strictly distinguished when designing the test.The manipulation of variables came to a mixed design of 2 (semantic types: core meaning, periphery meaning) × 2 (types of L1 translation equivalents: dominant L1 translation equivalent, non-dominant L1 translation equivalent) × 2 (language proficiency: low proficiency, high proficiency). The results showed that: (1) The semantic types and L1 translation equivalents had significant influence on the production of polysemous words in that the core meanings and the dominant L1 translation equivalent helped the learners access the words quickly and produce them more efficiently; The dominant L1 translation equivalents could facilitate the production of the words presented with their periphery meanings; (2) On the whole, there was no significant difference of the productive competence between the two groups of participants. Comparatively, the high proficiency learners performed better in the production of words presented in their periphery meanings corresponding to non-dominant L1 translation equivalents. And they showed a less degree of dependence on L1 translation equivalents in the process of language production.